Describe Your Feelings: Body Illusion Related to Alexithymia in Adolescence - Georgiou, Eleana; Mai, Sandra; Pollatos, Olga (Frontiers in Psychology, 2016)
Objective: Having access to bodily signals is known to be crucial for differentiating the self from others and coping with negative feelings. The interplay between bodily and emotional processes develops in adolescence, where vulnerability is high, as negative affect states often occur, that could hamper the integration of bodily input into the self. Aim of the present study in healthy adolescents was to examine, whether a disturbed emotional awareness, described by the alexithymic construct, could trigger a higher malleability in the sense of body-ownership. Methods: 54 healthy adolescents aged between 12 to 17 years participated in this study. The SDQ and the SPS-J were used to assess emotional distress and conduct problems. Alexithymia was assessed by the TAS-20. The rubber hand illusion was implemented for examining the malleability of body ownership. Results: A higher body illusion was found to be connected with “difficulties in describing feelings”. Moreover, a higher degree of self-reported conduct and emotional problems as assessed by the SDQ were associated with a more pronounced body illusion. Further findings revealed an association between emotional distress and the emotional alexithymia subscales “difficulties in identifying feelings” and “difficulties in describing feelings”. Conclusions: Our findings emphasize a close link between the sense of body-ownership and emotional awareness as assessed by emotional facets of the alexithymic trait. We suggest that in adolescents with higher malleability of body ownership, a vicious circle might occur where affect and integration of different proprioceptive signals regarding the body become more entangled.